Individual and team performance levels at major international target archery competitions, 2010-2017 - Park, J. L. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2019)
Major international target archery competitions include World Cups, World Championships and the Olympic Games. These events include both a 72-arrow ranking round and then one-on-one ranked knockout matches, until one archer or a team remains. To win either an event or at least a podium position, it is necessary for the archer or team to do very well in the ranking round. This article considers the individual, three-archer team and mixed team events over the period 2010-2017 and provides score objectives for each of them for future years and for the World Championships in 2019.